Assessment of E-Waste Management on Records Management of Messy Bessy Cleaners Inc.: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research focused on the Assessment of E-waste Management on RecordsManagement of Messy Bessy Cleaners Inc. Records are essentially valuable to a company'soperation, as well as organizing and keeping records is essential for the business to sustainits operation (Premakaruma, 2016). E-waste issues and measures become a challenge toentities. The researchers conducted an assessment of e-waste management to assess thecompany's e-waste issues and measures and the effect on records management to provideawareness and possible improvements (Lansang, 2019). Messy Bessy was chosen to bestudied as they have a need to improve e-waste management in their records management.This study revealed that the problems encountered by the respondents give rise to having arecords officer who will focus on records and E-waste management, wherein the recordsofficer is recommended to Plan, Create, Implement, and Evaluate standard guidelines to beused in records and E-waste Issues and measures.In accordance with the findings of the study, the research shows that Messy Bessyemployees encounter problems in assessing e-waste due to a lack of knowledge to processe-waste management. The result of the research revealed that Messy Bessy has a need toaddress the problems encountered in E-waste Management to provide solutions. TheDemographic Profile of the respondents does not affect the process of assessing E-wasteManagement.
Keywords: Business Administration